Holistic Competencies of Islamic Religious Teachers and Their Impact on Student Understanding in Secondary Schools - Izzah, Evti Annisa’ul; Layyinnati, Idzi’ (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study explores the significance of Islamic Religious Education teachers' competencies in enhancing students' understanding of religious values and shaping their character. Focusing on the pedagogical, professional, personal, and social aspects, the study investigates how these competencies directly affect students' comprehension of Islamic teachings. Using a qualitative descriptive approach with a case study design, this research was conducted at MA Muhammadiyah 06 Payaman in Indonesia. The data in this study were obtained from various sources, including primary data from classroom observation, interviews and document analusis, while secondary data were gathered from literature references and school academic reports. Data collection was conducted through classroom observations, interviews with teachers and students and analysis of relevant documents. The data analysis technique employed thematic analysis, following the steps of data analysis proposed by Miles and Huberman. The findings demonstrate that teachers' holistic competencies play a crucial role in improving students' understanding of religious concepts, while also fostering moral development. The study contributes to the literature on the transformation of Islamic education, offering insights into how teacher competencies shape students' educational experiences. Furthermore, it provides recommendations for educational institutions to focus on teacher development to address the challenges of the digital era while maintaining the quality of Islamic education.character and strengthening Islamic education as a whole.